PENGEMBANGAN DAN PENERAPAN MEDIA MONOPOLY BERVISI SETS PADA BIDANG STUDI GEOGRAFI MATERI MITIGASI DAN ADAPTASI BENCANA SEBAGAI INOVASI DALAM PENDIDIKAN KEBENCANAAN - Andika Triwidada; Khairuddin .; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The development and application of monopoly media is expected to build knowledge, skills and attitudes to encounter disasters. Integrated disaster education in the field of Geography studies, on the basic competencies of analyzing mitigation and adaptation to natural disasters. This research aims to describe the development and application of SETS visionary monopoly media in the field of geography studies on disaster mitigation and adaptation material. Media development uses a research design using the DDDMD approach (define, design, develop, manufacturing, disseminate), application using the control class approach and experimental class. As a result of the design development, Monopoly's visual media communication was 85.73% "very good". The average score of learning activities of students using Monopoly media is 86% "very good". The response of students and teachers to geography learning activities using Monopoly media was 89% "very good" and for the teacher's response 92% "very good". The product's resistance level is 93% "very good". Effectiveness of learning with the results of the achievement of learning completeness of students 100% complete with the results of posttest average score of 77.7. Overall, the development and application of the Monopoly media was 86% "very good".